The role of GLP-1 receptor agonists in obese patients with Polycystic Ovary Syndrome: an integrative review of the literature (Research, Society and Development, 2023)
Introduction: Polycystic Ovary Syndrome (PCOS) is associated with ovarian dysfunction, hyperandrogenism and insulin resistance (IR). It is known that obesity is one of the main factors related to the causes of IR, so the treatment of both involves, in association or not with pharmacological options, weight loss measures. Currently, there is no specific medication to treat PCOS and, therefore, the option of using GLP-1 receptor agonists (GLP-1RAs) in this combination corresponds to the objective of the present work. Methodology: This is an integrative review on the use of GLP-1RAs in obese patients with PCOS. Data from the Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO) and National Library of Medicine (PubMed) databases were used, by crossing the descriptors “Polycystic Ovary Syndrome”, “Obesity”, “Treatment”, “Liraglutide” and “GLP-1 receptor agonists”, to answer the question formulated through the PICO strategy. Results and Discussion: PCOS is a condition independent of obesity, but extremely stimulated by it. In the treatment of PCOS, metformin is commonly used, but studies have demonstrated the superiority of GLP-1RAs in reducing BMI, waist circumference and weight, however, regarding menstrual frequency, there are still doubts. Therefore, the association of the two drug options has proven to be beneficial. Conclusion: The association of obesity/IR and PCOS intensifies the disease and the use of GLP-1RAs is mostly beneficial in obese or overweight patients. However, research is needed to find a more effective treatment.